Comparison of Intramedullary Nail Fixation and Minimally Invasive Plate Osteosynthesis in Distal Tibial Fractures in Geriatric Patients - Uğur Onur Kasman (Sakarya Tıp Dergisi)
Introduction: Minimally invasive plate osteosynthesis (MIPO) and intramedullary nails are two accepted and effective methods in the treatment of tibial fractures. This study was aimed to evaluate the surgical treatment and complications of distal tibial fractures not related to the ankle joint with MIPO and intramedullary nails in the geriatric group retrospectively.Materials and Methods: Between 2019 and 2020, 42 patients in the geriatric group with distal tibia fractures that did not extend to the ankle joint and who underwent surgical treatment were evaluated retrospectively. The patients were divided into two groups: those who underwent MIPO and those who underwent osteosynthesis with an intramedullary nail. Patients were evaluated according to Johner Wrush criteria.Results: This study enrolled 42 patients. The mean age of the patients was 70±3.4 years. 22 of these patients underwent osteosynthesis with intramedullary nailing. MIPO was performed in the treatment of 20 patients. Based on the Johner Wrush criteria, the intramedullary nail group evaluated 16 patients as very good, 5 as good, and 1 as bad. The MIPO group evaluated 15 patients as excellent, 3 as good, 1 as moderate, and 1 as poor.Conclusion: In geriatric age groups, there was no significant difference in clinical outcomes or complications from surgical treatment of closed tibial distal fractures that do not extend to the ankle joint. Both surgical treatment methods can be applied effectively to geriatric patients.